Healthy habits: The connection between diet, exercise, and locus of control - Deborah A. Cobb-Clark; Sonja C. Kassenböhmer; Stefanie Schurer (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the relationship between individuals' locus of control and their decisions to exercise regularly, eat well, drink moderately, and avoid tobacco. Our primary goal is to assess the relative importance of the alternative pathways that potentially link locus of control to healthy habits. We find that individuals with an internal locus of control are more likely to eat well and exercise regularly. This link cannot be explained by the extent to which they are future-orientated and value their health, however. There are important gender differences in explaining the link between perceptions of control and healthy habits. Men with an internal locus of control expect to have higher health returns to their investments in diet and exercise. In contrast, women with an internal locus of control maintain healthy habits because they derive greater satisfaction from those activities than women with external control tendencies.
Keywords: I14; J3; C18; 330; non-cognitive skills; locus of control; health behavior; health diet; exercise